PENGEMBANGAN SISTEM PERTANIAN TERPADU MINA MENDONG METODE TERAS DALAM DI DESA WAJAK, KECAMATAN WAJAK - Silistyo, M. Adri Budi; ', Taufikkurrahman (Fakultas Teknik Universitas Wisnuwardhana, 2015)
Tilapia fish farming has been developed group of fish farmers in the village have not been enough to increase the economy Wajak fish farmers. This fact has influenced by the only income derived farmed tilapia and the process is substandard, depending on the payment of fish traders who are often in arrears. On the other hand, the declaration of the District Wajak as craft centers rushes, to encourage villagers to develop the program. The obstacles of fish farmers are difficulties in implementing rushes crop cultivation technology, because they only worked in the fishery. For it is based on mutual agreement between the team proposer and fish farmer groups as partners, agreed to implement integrated farming systems diversification program based fish-rushes (mina mendong), which combines fish farming with crop cultivation land rushes in one area. The program aims to optimize the potential of land, which had been used only for farming tilapia, with the modification of field through innovation mina mendong that combines farming of tilapia with the cultivation of land rushes in the same areas and the method as the deep terrace. Methods of implementation mina mendong done with several methods such as: firstly, extension methods of diversification based integrated farming system mina mendong, secondly demo plot of mina mendong, thirdly, giving technical assistance for the maintenance and supervision of the system mina mendong to produce products that can be harvested. The result is increase in income of fish farmers because the diversifications of products are not only tilapia harvested but also plant rushes in the same land. Average income of fish farmers using mina rushes for one year (1 ha) as much as Rp 140 million with a profit of Rp 73.64 million (B / C = 1.11), while cultivating mendong get revenue of Rp 48,000,000 with a profit 23,000,000 (B / C = 0.98).